2019
DOI: 10.1097/bot.0000000000001641
|View full text |Cite
|
Sign up to set email alerts
|

Indications and Clinical Results of Radial Head Replacement: Has Anything Changed?

Abstract: Summary: Radial head fractures are common injuries comprising 1/3 of the fractures about the elbow. As a secondary valgus stabilizer of the elbow, radial head fractures can compromise elbow stability leading to long-term pain, dysfunction, and degenerative change. Furthermore, radial head fractures can be accompanied by associated injuries including ligamentous lesions that can further exacerbate elbow instability, leading to long-term sequelae. As fixation principles and technology have evolved, so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The latter is usually reserved for type III fractures associated with ligamentous injury or proximal ulna fractures. 15 Although radial head resection is not the gold standard for treatment of complex radial head fractures, 16 there are clinical scenarios in which it may be the only feasible surgical procedure. These include open fracture dislocation of the elbow, incongruent proximal radioulnar joint, cartilage damage to the capitellum, or nonreconstructable radial head fractures with a proximal extension to the shaft.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is usually reserved for type III fractures associated with ligamentous injury or proximal ulna fractures. 15 Although radial head resection is not the gold standard for treatment of complex radial head fractures, 16 there are clinical scenarios in which it may be the only feasible surgical procedure. These include open fracture dislocation of the elbow, incongruent proximal radioulnar joint, cartilage damage to the capitellum, or nonreconstructable radial head fractures with a proximal extension to the shaft.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found that few patients undergoing radial head arthroplasty reported greater pain (VAS > 50 points) 1 month after surgery. Therefore, we regard 50 points as the cut‐off scores of the pain level 21,22 . For patients who present disproportionate pain in the operated limb, we initially attempted to exclude other potential causes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we regard 50 points as the cut‐off scores of the pain level. 21 , 22 For patients who present disproportionate pain in the operated limb, we initially attempted to exclude other potential causes. Second, we diagnosed CRPS I according to Budapest criteria, 23 which includes four categories (sensory, vasomotor, sudomotor/edema, motor/trophic).…”
Section: Methodsmentioning
confidence: 99%
“…Radial head (RH) and neck fractures are common and account for approximately one third of all elbow fractures. 1 3 They typically occur following a fall on an outstretched arm with the forearm in pronation, and fracture of the RH results from impaction on the capitellum. 4 Conservative treatment is used for nondisplaced fractures, with surgery reserved for more severe cases.…”
Section: Introductionmentioning
confidence: 99%